KOMUNIKASI TERAPEUTIK DALAM BIMBINGAN DAN KONSELING ISLAM - Fahrul Hidayat; Arisatul Maulana; Doni Darmawan (UIN Sunan Kalijaga Yogyakarta, 2019)
AbstractGuidance and counseling services is a service intended for all people, meaning that anyone can accept this service. However, service delivery must be done by people who are truly professionals who understand the techniques and methods of implementation. The guidance and counseling process is a service that always prioritizes communication. Communication is a vital tool that must be considered by the counselor. For that communication must be built as comfortable as possible by the counselor. One of the things that supports the success of the guidance and counseling service process is the therapeutic communication atmosphere, which means that the atmosphere is focused on healing the client. Therapeutic is basically known in the world of nursing but at this time therapeutic is also beginning to be known in the guidance and counseling services. In this study, we conducted a literature study that discusses therapeutic communication that can be done in counseling and guidance services. The conclusion of this study is that therapeutic communication is in principle a professional communication that leads to the goal. To be able to carry out the therapeutic communication process effectively, counselors need to master communication techniques. In its actualization, therapeutic communication is used by the counselor to instill confidence in the counselee and create a close relationship between the two in order to be able to open themselves to each other in handling problems and then the goals to be achieved can be implemented to the maximum.Keywords: communication, guidance and counseling, therapeutic.